Dilated cardiomyopathy in dystrophic epidermolysis bullosa. Issue 1 (1st July 2000) - Sidwell, R U; Yates, R; Atherton, D
Abstract : BACKGROUND: Dystrophic epidermolysis bullosa (DEB) is an uncommon genetic disorder of the skin and mucosae. In 1996, we reported the occurrence of lethal dilated cardiomyopathy (DCM) in two affected children. METHODS: In the past seven years we have routinely screened patients with severe DEB who have been under the care of this hospital by yearly clinical review, echocardiography, and quantification of plasma selenium and carnitine concentrations, as deficiency of these micronutrients is known to be associated with the development of DCM. RESULTS: Six of 61 children have developed DCM over the seven year period of this study, four of whom have not been previously reported, and three of whom have since died. We compared the concentrations of selenium and free and total carnitine in the children who developed DCM to concentrations in those with severe DEB who did not. The concentrations of free and total carnitine when first measured were significantly lower in the children with DCM, but the selenium concentrations were not. CONCLUSIONS: We now believe that DCM is a not infrequent complication of severe recessive DEB, and may be related in part to carnitine concentrations, though the exact mechanism remains unclear. We therefore recommend that patients with this condition should undergo regular cardiac review including echocardiography.